Potentiality of income generation through Non-timber Forest Products: A case study from the Sallipatan Trishakti Community Forest, Bajhang district, Nepal - Singh, Jeewan; Miya, Mahamad Sayab; Adhikari, Amit; Das, Lalit Kumar (International Research Journal of MMC, 2021)
Non-timber Forest Products are the major source of livelihood support for rural communities in Nepal. A case study was performed to determine the potentiality of income generation through Non-timber Forest Products (NTFPs) in the Sallipatan Trishakti community forest of Bajhang district, Nepal from February to April 2020. The Questionnaire surveys, key informant surveys, focus group discussions and forest resource inventory have been used for the data collection. A total of 37 species of NTFPs from 31 families were identified out of which only five species were found to have high market potential. Xanthoxylum armatum (Timur), Phyllanthus emblica (Amala), and Cinnamomum tamala (Tejpat) were found in good frequency and have a good market but the yearly earnings and the number of households involved were low. Bergenia ciliate (Pakhanbed), Valeriana jatamansi (Sugandhawal), and Rhododendron arboretum (Lali gurans) were present in high density in the forest and have high market value but locals didn’t prefer and market them due to lack of knowledge and processing technology. Among the total respondents, 59% collect NTFPs for household purposes, 30% for selling purposes, and 11% for traditional uses. Pinus roxburghii, Myrica esculenta, Swertia chirayita, Rhododendron arboretum, Cinnamomum tamala, Drepanostachyum sps., Asparagous racemous and Taxus wallichiana would have the potentiality for small scale business from the community forest if they were promoted and managed properly.